The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/ece3.3826
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent, negative heterozygosity–fitness correlations and local effects in an endangered Caribbean reptile, Iguana delicatissima

Abstract: Inbreeding depression can have alarming impacts on threatened species with small population sizes. Assessing inbreeding has therefore become an important focus of conservation research. In this study, heterozygosity–fitness correlations (HFCs) were measured by genotyping 7 loci in 83 adult and 184 hatchling Lesser Antillean Iguanas, Iguana delicatissima, at a communal nesting site in Dominica to assess the role of inbreeding depression on hatchling fitness and recruitment to the adult population in this endang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…According to a meta‐analysis conducted by Miller and Coltman (), our low g 2 as well as low HHC values should indicate weak HFCs, which could be difficult to detect. Our number of microsatellite loci used (15) is low, but close to the average of other HFC studies (Chapman et al, ; Miller & Coltman, ), and our number of genotyped individuals ( N = 7,974) far exceeds the published range (7–1,055), such that our number of genotypes (7,974 individuals × 15 markers = 119,610 genotypes; Slate et al, ) is more than double the highest number of genotypes (573 individuals × 101 markers = 57,873 genotypes; Slate et al, ) of all studies reviewed in Chapman et al (; also see Harrison et al, ; Judson, Knapp, & Welch, ; Monceau et al, ; Shaner et al, ; Soulsbury & Lebigre, ; Velando et al, ; Voegeli, Saladin, Wegmann, & Richner, for examples of more recent studies using a similar or even lower number of loci for estimating HFCs). The low number of loci used, associated with the weak HFCs detected, could prevent the detection of local effects (Szulkin et al, ), but, as also stated by Szulkin et al (), although a larger number of loci provide a more precise inbreeding estimate, a lower number of markers should not be used as an argument to invalidate significant findings.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…According to a meta‐analysis conducted by Miller and Coltman (), our low g 2 as well as low HHC values should indicate weak HFCs, which could be difficult to detect. Our number of microsatellite loci used (15) is low, but close to the average of other HFC studies (Chapman et al, ; Miller & Coltman, ), and our number of genotyped individuals ( N = 7,974) far exceeds the published range (7–1,055), such that our number of genotypes (7,974 individuals × 15 markers = 119,610 genotypes; Slate et al, ) is more than double the highest number of genotypes (573 individuals × 101 markers = 57,873 genotypes; Slate et al, ) of all studies reviewed in Chapman et al (; also see Harrison et al, ; Judson, Knapp, & Welch, ; Monceau et al, ; Shaner et al, ; Soulsbury & Lebigre, ; Velando et al, ; Voegeli, Saladin, Wegmann, & Richner, for examples of more recent studies using a similar or even lower number of loci for estimating HFCs). The low number of loci used, associated with the weak HFCs detected, could prevent the detection of local effects (Szulkin et al, ), but, as also stated by Szulkin et al (), although a larger number of loci provide a more precise inbreeding estimate, a lower number of markers should not be used as an argument to invalidate significant findings.…”
Section: Discussionsupporting
confidence: 76%
“…Because HFCs are expected to be strongest early in life (Koehn & Gaffney, ), many studies focused on early‐life stages (Annavi et al, ; Arct et al, ; Hansson, Bensch, Hasselquist, & Akesson, ; but see Höglund et al, ; Taylor & Jamieson, ; Velando et al, ). The few studies that did investigate different age classes mostly compared young/juvenile stages versus adult stages (Canal et al, ; Cohas et al, ; Judson et al, ; Lieutenant‐Gosselin & Bernatchez, ; Monceau et al, ; but see also Olano‐Marin et al, ; Von Hardenberg et al, ) and most of them found contrasting heterozygosity effects between classes. Interestingly, these studies only detected significant HFCs at the juvenile stage, most likely due to the selective mortality of the most homozygous individuals at this stage, and therefore contrast with our own.…”
Section: Discussionmentioning
confidence: 99%
“…In general, our results add to the increasing evidence that single-locus effects could underlie HFCs more than it was acknowledged earlier. Single-locus effects have been reported in previous HFC studies on wild-ranging animals (Hansson et al 2004;Lieutenant-Gosselin and Bernatchez 2006;Ortego et al 2007;Kaeuffer et al 2008;Fossøy et al 2009;Vangestel et al 2011;García-Navas et al 2014;Minias et al 2015;Judson et al 2018). However, only a few HFC studies related to disease documented local effects (Acevedo-Whitehouse et al 2006Amos and Acevedo-Whitehouse 2009) and, to our knowledge, our study is the first to show them in a diseaserelated study on a bird.…”
Section: Heterozygosity: Single-locus Effectssupporting
confidence: 48%
“…It is apparent from the genetic markers used in this study that there is a significant paucity of genetic diversity within the Anguillan I. delicatissima population with only one haplotype being identified in each of the four loci. This is perhaps not surprising as other studies have demonstrated a lack of unique haplotypes between geographically isolated populations (Day and Thorpe 1996;Martin et al 2015;Stephen et al 2012), and has also been reported in the populations on St Eustatius, Dominica and the French West Indies (Judson et al 2018;van den Burg et al 2016;Vuillaume et al 2015). Other genetic markers such as microsatellites could be informative in understanding the structure and genetic diversity of a population, as well as estimating effective populations sizes (Valette et al 2013;van den Burg et al 2016), but this was not an objective of the current study.…”
Section: Genetic Diversity Of Anguillan Iguana Populationsmentioning
confidence: 68%